Cooperative business-NGO partnerships in Hong Kong: NGO perspective. (26th June 2007) - Kaur Mantel, Sukhmani; Cheung, Dennis; Welford, Richard; Hills, Peter
Over the past decade, processes of environmental reform have been increasingly shaped by cooperative management between businesses, government and NGOs. This paper provides results of extensive interviews to assess cooperative environmental relationships between businesses and NGOs in Hong Kong and the barriers and positive drivers for these partnerships. Interviews with ten partnering NGOs found most optimistic about what has been achieved. Non-partnering NGOs interviewed were also hopeful about future partnerships. Overall, NGOs expressed the need for capacity building on governance issues, on negotiating partnerships and hope that business associations and government can provide necessary support. Issues of weak economy, business dominated thinking, weak civil society and lack of top-level commitment to environment need addressing. Comparison of small and large NGOs showed similar gains and surprisingly even similar types of partnerships. This study identified Seven Skills for Partnership Success to build on Plante and Bendell's Art of Collaboration.